Terbium-doped transparent glass-ceramics containing TbPO4 crystals: A promising material for photonic applications - Franco, Douglas F. [UNESP]; Caixeta, Fábio J. [UNESP]; Albino, Leonardo V. [UNESP]; Lodi, Thiago A. [UNESP]; Orives, Juliane R. [UNESP]; Ghezzi, Eduardo O. [UNESP]; Nalin, Marcelo [UNESP] (Elsevier, 2023)
Glasses and glass-ceramics based on the Tb3+-doped SbPO4-GeO2-Al2O3 composition have been studied. Samples containing up to 0.4 mol % of Tb4O7 form glasses when obtained by melt-quenching while concentrations above that tends to form glass-containing single crystals. This work reports the thermal, structural, morphological, and optical studies of (96-x)(40SbPO4-60GeO2)-4Al2O3-xTb4O7 samples (where 0.2 ≤ x ≤ 0.7, in mol %) using Differential Scanning Calorimetry, X-ray Powder Diffraction, Scanning Electron Microscopy, Energy Dispersive Spectroscopy, UV–Vis absorption, Raman, and Photoluminescence spectroscopies. The diffraction pattern for the glass-ceramic containing 0.7 mol% of Tb4O7 shows diffraction peaks, which were assigned to the crystalline phase derived from terbium orthophosphate (TbPO4). In the same direction, the Raman spectra of the glass-ceramics containing 0.5, 0.6, and 0.7 mol% of Tb4O7 exhibited narrow bands in the region between 900 and 1300 cm-1, which are characteristic of the main vibrational modes of the PO4 tetrahedral units of TbPO4. The TbPO4 crystals exhibited an average size distribution ranging from 10 to 200 μm. The TbPO4 crystals exhibited an unusual morphology and design, resembling the shape of the letter “H” and is completely different from the crystals reported in the literature. Strong green emission from TbPO4 crystals was verified at 547 nm for all samples. The emission spectra showed not only bands assigned to 5D4→7FJ electronic transitions in the green-red range, but also those coming from 5D3→7FJ in blue region.
Keywords: Glass-ceramics; Glasses; Luminescence; Terbium orthophosphate